Functions of the Tropes in Jassim Al-Sahhih’s poetry - Alhajjaji, Amani Ahmad Mohammad (Journal of Arabic Language Sciences and Literature, 2025)
This study aims to address the functions of image in Jassim Al-Sahih’s poetry, by examining the aesthetic functions, from examples of his complete poetic works, according to the descriptive analytical approach, based on complete and partial conclusions. It is a general deduction in extracting literary phenomena and setting standards for the aesthetics of the text, and this is evident in monitoring the beauty of describing the image, and tracking the creative ability of the narrator, which is useful for partial analyzes of the text. This is what the study adopted in tracking its merits, and the study concluded with a number of results, including: the interest of the aesthetic function in knowing the nucleus of the poet Jassim Al-Sahih’s familiarity with employing many values and rhetorical arts, investigating the patterns of the sensory image and employing the Al-Sahih poem for the senses (visual, auditory, gustatory, and olfactory), Trace the words of the image and the characteristics of the words of its poetic lexicon. Through the societal environments on which the poet’s culture is based, from the history of the Arabs from originality to civilization, which Jassim Al-Sahih employed in his poetic images. The study also recommends expanding the study of the images of Jassim Al-Sahih’s poetry.
Keywords: Arabic poetry; functions of the poetic image; poet Jassim Al-Sahhih